Electrode material and preparation method thereof, electrode, battery, flexible transparent carbon fiber net and preparation method thereof, capacitor, electronic device
By growing cobalt complexes in situ on silk and heat treatment, nitrogen-doped porous carbon-based electrode materials and flexible transparent carbon fiber webs were prepared, which solved the problem of insufficient flexibility of lithium-ion batteries in flexible foldable electronic devices, and realized the material The flexibility, electrochemical properties and light transmittance are both.
Patent Information
- Application Number
- CN202411419507.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The existing lithium-ion batteries have low tensile strain and insufficient flexibility, and are prone to damage after multiple bending tests, making it difficult to meet the needs of flexible foldable electronic devices.
By growing cobalt complexes in situ on silk and heat treatment at high temperatures, a nitrogen-doped porous carbon-based electrode material was prepared, and a flexible transparent carbon fiber web was prepared in combination with an acid etching step.
It realizes that the electrode material and flexible transparent carbon fiber web have both flexibility, excellent electrochemical properties and light transmittance, and can maintain normal operation after multiple bends, and is suitable for flexible foldable electronic devices.
Smart Images

Figure CN118919705B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery electrode materials and capacitor materials, and in particular to an electrode material and a preparation method thereof, an electrode, a battery, a flexible transparent carbon fiber mesh and a preparation method thereof, a capacitor, and an electronic device. Background Art
[0002] With the continuous development of science and technology, various types of portable electronic devices are playing an increasingly important role in daily life, and their functions are becoming more and more diversified. While improving the user experience, they also put forward higher requirements on their energy supply and energy storage devices. Lithium-ion batteries have relatively mature production technology and higher energy density than other types of batteries. They can be charged and discharged repeatedly, and are environmentally friendly. They have become the first choice for power sources for flexible wearable devices and mobile portable electronic devices. However, with the continuous improvement of user demand, one of the ultimate development directions of portable electronic devices may be flexible and foldable, which can further save space while ensuring the user experience. This requires that its energy supply device should also have corresponding flexibility. However, the battery components of commercial lithium-ion batteries at this stage have low tensile strain and relatively insufficient flexibility, and they are damaged after multiple bending tests. Summary of the invention
[0003] The object of the present invention is to overcome one or more deficiencies in the prior art and to provide an improved method for preparing an electrode material that has flexibility, excellent electrochemical properties and light transmittance.
[0004] The present invention also provides an electrode material prepared by the above method, and an electrode and a battery comprising the electrode material.
[0005] The present invention also provides an improved method for preparing a flexible transparent carbon fiber mesh having flexibility, excellent electrochemical properties and light transmittance, the prepared flexible transparent carbon fiber mesh, and a capacitor comprising the flexible transparent carbon fiber mesh.
[0006] The present invention also provides an electronic device comprising the battery or capacitor, so that the electronic device can have flexible and foldable properties.
[0007] In order to achieve the above object, a technical solution adopted by the present invention is: a method for preparing an electrode material, the preparation method comprising:
[0008] Applying cobalt nitrate and the compound represented by formula (I) on silk respectively, growing a cobalt complex in situ on the surface and / or in the pores of the silk, and forming silk loaded with the cobalt complex;
[0009] In formula (I), R1 and R2 are independently selected from C 1-3Alkyl, n is 0, 1 or 2;
[0010] The silk loaded with the cobalt complex is heat treated at 700-950° C. under a protective atmosphere to obtain the electrode material;
[0011] The electrode material comprises nitrogen-doped porous carbon and nano-metal cobalt supported on the surface of the nitrogen-doped porous carbon and / or encapsulated in the pore structure of the nitrogen-doped porous carbon.
[0012] According to some preferred and specific aspects of the present invention, the preparation method further comprises:
[0013] Separately prepare a cobalt nitrate solution and a solution of the compound represented by formula (I);
[0014] The silk is first immersed in one of the cobalt nitrate solution and the solution of the compound represented by formula (I), and then immersed in the other one.
[0015] In some embodiments of the present invention, the cobalt nitrate solution and the solution of the compound represented by formula (I) respectively use water as solvent.
[0016] According to some specific aspects of the present invention, the molar concentration of the cobalt nitrate solution is 0.5-1.5 mol / L, for example, it can be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, etc.
[0017] According to some specific aspects of the present invention, the molar concentration of the solution of the compound represented by formula (I) is 1.5-3.0 mol / L, for example, it can be 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2.0 mol / L, 2.1 mol / L, 2.2 mol / L, 2.3 mol / L, 2.4 mol / L, 2.5 mol / L, 2.6 mol / L, 2.7 mol / L, 2.8 mol / L, 2.9 mol / L, 3.0 mol / L, etc.
[0018] According to some preferred aspects of the present invention, the silk is first soaked in the cobalt nitrate solution for X1 min, and then soaked in the solution of the compound represented by formula (I) for X2 min, X1:X2=1.5-3:1.
[0019] In some embodiments of the present invention, X1 is 15-25, and X2 is 5-15.
[0020] In some embodiments of the present invention, R1 is selected from methyl, ethyl or propyl, and n is 0.
[0021] In some embodiments of the present invention, R1 and R2 are independently selected from methyl, ethyl or propyl, and n is 1 or 2.
[0022] According to some specific aspects of the present invention, the compound represented by formula (I) is a combination of one or more selected from 2-methylimidazole, 2-ethylimidazole, and 2-propylimidazole.
[0023] According to some preferred aspects of the present invention, the added amount of the cobalt nitrate is controlled to load 0.015-0.05 mmol per square centimeter of the silk.
[0024] According to some preferred aspects of the present invention, the added amount of the compound represented by formula (I) is 0.03-0.1 mmol per square centimeter of the silk.
[0025] In some embodiments of the present invention, the silk is made of mulberry silk. According to a specific aspect of the present invention, the silk is commercial mulberry silk with a specification of 5.5 momme.
[0026] In some embodiments of the present invention, the preparation method further comprises: before the heat treatment, washing the silk loaded with the cobalt complex and performing a drying treatment.
[0027] In some embodiments of the present invention, the cleaning is performed using deionized water.
[0028] In some embodiments of the present invention, the drying process is vacuum drying. Further, the drying process temperature is 50-70° C. Further, the drying process time is 1-3 hours.
[0029] According to some preferred aspects of the present invention, the heat treatment is performed at 750-850°C.
[0030] In some embodiments of the present invention, the heat treatment time is 1-6 hours, further 1-3 hours.
[0031] According to the present invention, the nitrogen-doped porous carbon is a carbon fiber mesh structure formed by interweaving a plurality of carbon fibers.
[0032] According to the present invention, the electrode material is in a transparent state.
[0033] In some embodiments of the present invention, the diameter of the carbon fiber is 30-500 nm, further 100-200 nm.
[0034] Another technical solution provided by the present invention is: an electrode material prepared by the above-mentioned method for preparing the electrode material.
[0035] Another technical solution provided by the present invention is: an electrode, wherein the electrode comprises the electrode material described above.
[0036] Another technical solution provided by the present invention is a battery, comprising a positive electrode and a negative electrode, wherein either the positive electrode or the negative electrode is the electrode described above.
[0037] Furthermore, the battery is a lithium-ion battery.
[0038] Another technical solution provided by the present invention is a method for preparing a flexible transparent carbon fiber mesh, the preparation method comprising:
[0039] Applying cobalt nitrate and the compound represented by formula (I) on silk respectively, growing a cobalt complex in situ on the surface and / or in the pores of the silk, and forming silk loaded with the cobalt complex;
[0040] In formula (I), R1 is C 1-3 Alkyl, R2 is H or C 1-3 Alkyl, n is 1 or 2;
[0041] The cobalt complex-loaded silk is heat-treated at 700-950° C. under a protective atmosphere to obtain an intermediate;
[0042] Then, the intermediate is subjected to acid etching to obtain the flexible transparent carbon fiber mesh.
[0043] Further, the acid etching is carried out with hydrochloric acid. In some embodiments of the present invention, the molar concentration of the hydrochloric acid can be 0.5-3mol / L, for example, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, 1.5mol / L, 1.6mol / L, 1.7mol / L, 1.8mol / L, 1.9mol / L, 2.0mol / L, 2.1mol / L, 2.2mol / L, 2.3mol / L, 2.4mol / L, 2.5mol / L, 2.6mol / L, 2.7mol / L, 2.8mol / L, 2.9mol / L, 3.0mol / L, etc.
[0044] According to some specific aspects of the present invention, the etching time of the acid etching is controlled to be 10-60 minutes.
[0045] In some embodiments of the present invention, the flexible transparent carbon fiber mesh has a pore structure with a size of 20-30 nm.
[0046] In some embodiments of the present invention, the protective atmosphere is formed by introducing nitrogen and / or an inert gas.
[0047] Another technical solution provided by the present invention is a flexible transparent carbon fiber net made by the above-mentioned preparation method of the flexible transparent carbon fiber net.
[0048] Another technical solution provided by the present invention is: a capacitor, comprising a positive electrode, a negative electrode, and an electrolyte between the positive electrode and the negative electrode, wherein either the positive electrode or the negative electrode comprises the above-mentioned flexible transparent carbon fiber mesh.
[0049] Another technical solution provided by the present invention is: an electronic device, wherein the electronic device comprises the battery or the capacitor described above.
[0050] Furthermore, an electronic device including the battery or the capacitor described above can help to make a flexible and foldable portable electronic device or a wearable electronic device.
[0051] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0052] Silk is a common biomass material with a very large annual output. The structure of silk is composed of silk protein and sericin. Under high temperature conditions, the protein molecules are rearranged during the pyrolysis process. In the present invention, by controlling the temperature of the heat treatment, the protein molecules of silk are transformed into sp with a graphite-like crystal layer structure. 2 Hybridized carbon hexagonal structure, thus forming a conductive material, which also contains a high content of nitrogen;
[0053] The present invention loads a cobalt complex formed by cobalt and a nitrogen-containing imidazole compound on silk before heat treatment, and especially deposits the cobalt complex uniformly on the surface and pores of silk fibers by an in-situ synthesis method. After heat treatment, not only a transparent and flexible porous carbon-based electrode material can be prepared, but also the ligands of the complex and the silk can generate nitrogen-doped porous carbon during the calcination process, and the cobalt ions are reduced to nano-metal cobalt and loaded on the surface of the porous carbon and / or encapsulated in the pore structure of the porous carbon; further, when the electrode material after heat treatment is acid-etched by etching, the prepared material is helpful for use as an electrode in a capacitor.
[0054] The lithium battery prepared based on the above materials and / or methods has good rate and cycle performance, and less polarization phenomenon; the material also exhibits good electrochemical properties, light transmittance and flexibility when used to prepare capacitors.
[0055] Furthermore, the present invention can achieve the following technical effects:
[0056] (1) The materials are readily available, low cost, and the preparation process is simple, making it suitable for large-scale production.
[0057] (2) As a transparent negative electrode for preparing lithium batteries, its initial reversible capacity can reach 1060 mAh g -1 The discharge voltage platform is 0.75V, and its cycle performance is excellent (at 4A·g -1 After 475 cycles at a current density of 1.5 %, the battery capacity can still reach 1000 mAh g -1 above).
[0058] (3) As a transparent negative electrode to prepare a transparent capacitor, the surface capacitance of the capacitor is as high as 0.227mF / cm 2 , and it can still maintain 78% of its initial capacity after 2,000 cycles in the cycle stability test.
[0059] (4) In the bending test, after 200 bends, the electrode material, the flexible transparent carbon fiber mesh, and the capacitor made of the present invention can still work normally and are basically not damaged. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 Schematic diagram of the preparation process of the electrode material of the present invention;
[0061] Figure 2 The SEM and TEM images of the electrode material obtained after heat treatment during the preparation process of Example 1;
[0062] Figure 3 This is the XRD pattern of the electrode material obtained after heat treatment during the preparation process of Example 1;
[0063] Figure 4 This is a physical picture of the electrode material prepared in Example 1;
[0064] Figures 5 to 7 is a performance diagram of a lithium battery prepared based on the electrode material obtained in Example 1; wherein, Figure 5 is the rate performance of the battery at different current densities, Figure 6 This is the battery cycle performance test diagram. Figure 7 It is a battery voltage-capacity curve;
[0065] Figure 8 TEM image and HRTEM image of the flexible transparent carbon fiber mesh prepared in Example 5;
[0066] Fig. 9 This is a performance diagram of a capacitor prepared based on the transparent carbon fiber mesh obtained in Example 5;
[0067] Fig.10 A comparison chart of the capacitance of capacitors prepared from the flexible transparent carbon fiber mesh obtained in different embodiments (embodiments 5-8);
[0068] Fig.11 The graph is a graph showing the change in capacitance of the capacitor prepared based on the carbon fiber mesh obtained in Comparative Example 1 as a function of the number of cycles;
[0069] Fig.12 This is a comparison diagram of cyclic voltammetry curves of the capacitor constructed based on the flexible transparent carbon fiber mesh obtained in Example 5 after being bent 200 times. DETAILED DESCRIPTION
[0070] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.
[0071] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.
[0072] In the following description, silk refers to commercial mulberry silk with a specification of 5.5 momme, and cobalt nitrate solution and 2-methylimidazole solution refer to aqueous solutions.
[0073] Embodiment 1:
[0074] This example provides an electrode material and a preparation method thereof, and the preparation method of the electrode material comprises the following steps:
[0075] S1. First, prepare 30 mL of 1 mol / L cobalt nitrate solution, marked as solution A, and then prepare 30 mL of 2 mol / L 2-methylimidazole solution, marked as solution B;
[0076] S2, the size is 30×30cm 2 The silk was first immersed in solution A for 20 minutes, and then immersed in solution B for 10 minutes, and then cobalt-2-methylimidazole complexes were in situ grown on the surface and in the pores of the silk.
[0077] S3, washing the silk loaded with the cobalt complex with deionized water for three times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;
[0078] S4. The dried silk loaded with the cobalt-2-methylimidazole complex is placed in a tube furnace for heat treatment at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an electrode material.
[0079] Embodiment 2:
[0080] This example provides an electrode material and a preparation method thereof, and the preparation method of the electrode material comprises the following steps:
[0081] S1. First, prepare 30 mL of 0.5 mol / L cobalt nitrate solution, marked as solution A, and then prepare 30 mL of 1 mol / L 2-methylimidazole solution, marked as solution B;
[0082] S2, the size is 30×30cm 2 The silk was first immersed in solution A for 20 minutes, and then immersed in solution B for 10 minutes, and then cobalt-2-methylimidazole complexes were in situ grown on the surface and in the pores of the silk.
[0083] S3, washing the silk loaded with the cobalt complex with deionized water for three times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;
[0084] S4. The dried silk loaded with the cobalt-2-methylimidazole complex is placed in a tube furnace for heat treatment at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an electrode material.
[0085] Embodiment 3:
[0086] This example provides an electrode material and a preparation method thereof, and the preparation method of the electrode material comprises the following steps:
[0087] S1. First, prepare 30 mL of 0.75 mol / L cobalt nitrate solution, marked as solution A, and then prepare 30 mL of 1.5 mol / L 2-methylimidazole solution, marked as solution B;
[0088] S2, the size is 30×30cm 2 The silk was first immersed in solution A for 20 minutes, and then immersed in solution B for 10 minutes, and then cobalt-2-methylimidazole complexes were in situ grown on the surface and in the pores of the silk.
[0089] S3, washing the silk loaded with the cobalt complex with deionized water for three times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;
[0090] S4. The dried silk loaded with the cobalt-2-methylimidazole complex is placed in a tube furnace for heat treatment at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an electrode material.
[0091] Embodiment 4:
[0092] This example provides an electrode material and a preparation method thereof, and the preparation method of the electrode material comprises the following steps:
[0093] S1. First, prepare 30 mL of 1.5 mol / L cobalt nitrate solution, marked as solution A, and then prepare 30 mL of 3 mol / L 2-methylimidazole solution, marked as solution B;
[0094] S2, the size is 30×30cm 2 The silk was first immersed in solution A for 20 minutes, and then immersed in solution B for 10 minutes, and then cobalt-2-methylimidazole complexes were in situ grown on the surface and in the pores of the silk.
[0095] S3, washing the silk loaded with the cobalt complex with deionized water for three times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;
[0096] S4. The dried silk loaded with the cobalt-2-methylimidazole complex is placed in a tube furnace for heat treatment at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an electrode material.
[0097] Embodiment 5:
[0098] This example provides a flexible transparent carbon fiber mesh and a preparation method thereof, and the preparation method of the flexible transparent carbon fiber mesh comprises the following steps:
[0099] S1. First, prepare 30 mL of 1 mol / L cobalt nitrate solution, marked as solution A, and then prepare 30 mL of 2 mol / L 2-methylimidazole solution, marked as solution B;
[0100] S2, the size is 30×30cm 2 The silk was first immersed in solution A for 20 minutes, and then immersed in solution B for 10 minutes, and then cobalt-2-methylimidazole complexes were in situ grown on the surface and in the pores of the silk.
[0101] S3, washing the silk loaded with the cobalt complex with deionized water for three times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;
[0102] S4, heat-treating the dried silk loaded with the cobalt-2-methylimidazole complex in a tube furnace at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an intermediate;
[0103] S5. The intermediate is acid-etched using hydrochloric acid having a molar concentration of 1 mol / L for 30 minutes to obtain a flexible transparent carbon fiber mesh.
[0104] Embodiment 6:
[0105] This example provides a flexible transparent carbon fiber mesh and a preparation method thereof, and the preparation method of the flexible transparent carbon fiber mesh comprises the following steps:
[0106] S1. First, prepare 30 mL of 0.5 mol / L cobalt nitrate solution, marked as solution A, and then prepare 30 mL of 1 mol / L 2-methylimidazole solution, marked as solution B;
[0107] S2, the size is 30×30cm 2 The silk was first immersed in solution A for 20 minutes, and then immersed in solution B for 10 minutes, and then cobalt-2-methylimidazole complexes were in situ grown on the surface and in the pores of the silk.
[0108] S3, washing the silk loaded with the cobalt complex with deionized water for three times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;
[0109] S4, heat-treating the dried silk loaded with the cobalt-2-methylimidazole complex in a tube furnace at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an intermediate;
[0110] S5. The intermediate is acid-etched using hydrochloric acid having a molar concentration of 1 mol / L for 30 minutes to obtain a flexible transparent carbon fiber mesh.
[0111] Embodiment 7:
[0112] This example provides a flexible transparent carbon fiber mesh and a preparation method thereof, and the preparation method of the flexible transparent carbon fiber mesh comprises the following steps:
[0113] S1. First, prepare 30 mL of 0.75 mol / L cobalt nitrate solution, marked as solution A, and then prepare 30 mL of 1.5 mol / L 2-methylimidazole solution, marked as solution B;
[0114] S2, the size is 30×30cm 2 The silk was first immersed in solution A for 20 minutes, and then immersed in solution B for 10 minutes, and then cobalt-2-methylimidazole complexes were in situ grown on the surface and in the pores of the silk.
[0115] S3, washing the silk loaded with the cobalt complex with deionized water for three times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;
[0116] S4, heat-treating the dried silk loaded with the cobalt-2-methylimidazole complex in a tube furnace at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an intermediate;
[0117] S5. The intermediate is acid-etched using hydrochloric acid having a molar concentration of 1 mol / L for 30 minutes to obtain a flexible transparent carbon fiber mesh.
[0118] Embodiment 8:
[0119] This example provides a flexible transparent carbon fiber mesh and a preparation method thereof, and the preparation method of the flexible transparent carbon fiber mesh comprises the following steps:
[0120] S1. First, prepare 30 mL of 1.5 mol / L cobalt nitrate solution, marked as solution A, and then prepare 30 mL of 3 mol / L 2-methylimidazole solution, marked as solution B;
[0121] S2, the size is 30×30cm 2 The silk was first immersed in solution A for 20 minutes, and then immersed in solution B for 10 minutes, and then cobalt-2-methylimidazole complexes were in situ grown on the surface and in the pores of the silk.
[0122] S3, washing the silk loaded with the cobalt complex with deionized water for three times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;
[0123] S4, heat-treating the dried silk loaded with the cobalt-2-methylimidazole complex in a tube furnace at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an intermediate;
[0124] S5. The intermediate is acid-etched using hydrochloric acid having a molar concentration of 1 mol / L for 30 minutes to obtain a flexible transparent carbon fiber mesh.
[0125] Comparative Example 1:
[0126] This example provides a carbon fiber mesh and a preparation method thereof, and the preparation method of the carbon fiber mesh comprises the following steps:
[0127] S1, washing the silk without the cobalt-2-methylimidazole complex with deionized water for 3 times, flattening it and drying it in a vacuum drying oven at 60 degrees Celsius for 2 hours;
[0128] S2, heat-treating the dried silk without the cobalt-2-methylimidazole complex in a tube furnace at 800 degrees Celsius for 2 hours under nitrogen protection to obtain an intermediate;
[0129] S3. The intermediate is acid-etched using hydrochloric acid having a molar concentration of 1 mol / L for 30 minutes to obtain a carbon fiber mesh.
[0130] Performance Test:
[0131] The electrode material disclosed in the present invention is characterized in that a porous electrode structure is prepared by a simple and convenient in-situ synthesis of a cobalt-imidazole complex and then heat treatment. For the flexible transparent carbon fiber mesh, the preparation process of the electrode material is further combined with an acid etching method to prepare a porous transparent conductive carbon fiber mesh. They all have excellent electrochemical properties. When they are assembled into transparent lithium batteries and transparent capacitors, they all show good electrochemical performance. The electrode material is used as a transparent positive electrode to prepare a lithium battery (battery test: the positive electrode is made of the electrode material prepared by the present invention, the negative electrode is metal Li, and the electrolyte is a mixed solution of EC ethylene carbonate / DEC diethyl carbonate mixed in a volume ratio of 1:1 and added with LiPF6, and the concentration of LiPF6 is 1 mol / L), and its initial reversible capacity reaches 1060mAh·g -1 The discharge voltage platform is 0.75V; the lithium battery has excellent cycle performance, at 4A·g -1 After 475 cycles at a current density of 1.5 %, the battery capacity can still reach 1000 mAh g -1 Above. After the flexible transparent carbon fiber mesh was used as an electrode to prepare a capacitor (capacitor test electrolyte: ClNaO4 / PVA hydrogel), in the cycle stability test, the prepared capacitor can still maintain 78% of its initial capacity after 2000 cycles. The initial surface capacity of the capacitor is as high as 0.227mF / cm². In the bending test, after 200 bends, the capacitor can still work normally and is not damaged. Compared with the traditional preparation method, this manufacturing process has the advantages of simple material preparation, easy availability of raw materials, and low cost, and is suitable for large-scale production.
[0132] Figure 1 Schematic diagram of the preparation process of the electrode material of the present invention. The electrode material of the present invention is prepared by in-situ synthesis and heat treatment.
[0133] For the flexible transparent carbon fiber mesh, an acid etching step is added compared to the preparation process of the electrode material. The flexible transparent carbon fiber mesh and NaClO4 / PVA hydrogel electrolyte can be constructed into a transparent supercapacitor.
[0134] Figure 2 The SEM and TEM images of the electrode material obtained after heat treatment during the preparation process of Example 1. Figure 2 As shown in Figure a), the electrode material has a carbon fiber mesh structure, and the carbon fiber mesh is interwoven with carbon fibers with a diameter of 100-200nm, and the fibers are evenly and orderly distributed. Figure 2 As shown in Figure b), when a part of the carbon fiber mesh is magnified, it can be clearly observed that the nanoparticles are evenly distributed.
[0135] Figure 3This is the XRD pattern of the electrode material obtained after heat treatment in the preparation process of Example 1, which is completely consistent with the diffraction peak position of metal cobalt (PDF (standard diffraction card NO.): 00-015-0806), proving that a large number of metal cobalt nanoparticles are deposited on the surface of the electrode material.
[0136] Figure 4 This is a physical picture of the electrode material prepared in Example 1. When it is placed on a paper with letters, it can be seen that the blocked letters can be clearly seen through the electrode material in the form of a carbon fiber mesh, proving that the electrode material has good transparency.
[0137] Figures 5 to 7 This is a performance diagram of a lithium battery prepared based on the electrode material obtained in Example 1;
[0138] in, Figure 5 The rate performance of the battery at different current densities. As the current density increases, the specific capacity gradually decreases. In the first cycle, its initial reversible capacity reaches 1060 mAh g -1 As the rate increases, the specific capacity of the battery decreases significantly. When the current density returns to 1A·g -1 When the specific capacity is restored to 1100mAh g -1 Around, indicating that the battery has good rate recovery capability;
[0139] Figure 6 This is the battery cycle performance test diagram, at 4A·g -1 After 475 cycles at a current density of 1.34 W, the battery capacity can still reach 1070 mAh g -1 , showing relatively stable cycle performance;
[0140] Figure 7 The battery voltage-specific capacity curve is shown in Figure 2. In the first cycle, the charge-discharge curve changes greatly, indicating that the battery may have a solid electrolyte interface (SEI) film formed in the initial cycle. The second and third cycle curves are relatively overlapped, indicating that the electrochemical reaction of the battery tends to be stable, showing good reversibility and small polarization.
[0141] Figure 8 The TEM and HRTEM images of the flexible transparent carbon fiber mesh prepared in Example 5. The TEM image is the left image a), and the HRTEM image is the right image b). As shown in the figure, after etching with hydrochloric acid, the carbon fiber forms a rich porous structure with a pore size of about 20-30 nm, which can effectively increase the specific surface area of the flexible transparent carbon fiber mesh, effectively increase the amount of ion adsorption, and improve the capacitance.
[0142] Fig. 9 The performance diagram of the capacitor (NaClO4 / PVA hydrogel electrolyte) prepared based on the transparent carbon fiber mesh obtained in Example 5; wherein, Fig. 9 Figure a) is a cyclic voltammetry curve at different scan rates. The shape and area of the curve change with the increase of the scan rate, showing the electrochemical behavior of the capacitor at different scan rates. A higher scan rate leads to a larger current response, which is due to a faster charge / discharge process, indicating that the transparent carbon fiber mesh obtained by the present invention can be used to prepare a capacitor; Fig. 9 Figure b) is a cyclic voltammetry curve under different potential windows. It can be seen that as the potential window increases, the current response increases significantly, which is in line with the trend, further indicating that the transparent carbon fiber mesh obtained by the present invention can be used to prepare capacitors; Fig. 9 Figure c) shows the cyclic voltammetry curves at different cycle numbers. As the number of cycles increases, the shape and area of the cyclic voltammetry curves do not change much, indicating that the capacitor maintains good electrochemical stability and reversibility after multiple cycles. Fig. 9 Figure d) shows the change of capacitance with the number of cycles. The capacitance value gradually decreases with the increase of the number of cycles, from the initial about 221μF / cm 2 Reduced to about 172μF / cm 2 (2000 cycles), indicating a long service life; Fig. 9 Figure e) in the figure shows the constant current charge and discharge curves under different currents. Higher currents lead to shorter charge and discharge times, indicating the fast response capability of the capacitor under high currents.
[0143] Fig.10 The capacitance (current) comparison diagram of the capacitor prepared from the flexible transparent carbon fiber mesh obtained in different embodiments (Examples 5-8) is shown. It can be seen that with the increase in the concentration of the immersion solution, the capacitance first increases and then decreases, proving the role of the porous structure and ion adsorption in improving the capacitance. However, excessive metal cobalt deposition combined with acid etching may cause damage to the carbon fiber structure, thereby reducing the capacitance.
[0144] Fig.11 The capacitance of the capacitor prepared based on the carbon fiber mesh obtained in Comparative Example 1 changes with the number of cycles. It can be seen that the capacitance gradually decreases with the increase of the number of cycles, from the initial about 39 μF / cm 2 Reduced to about 27μF / cm 2 (2000 cycles). Compared with Example 5, the initial capacitance of the capacitor constructed by the carbon fiber mesh prepared without loading the cobalt complex is only about 17% of the supercapacitor constructed by the flexible transparent carbon fiber mesh prepared with loading the cobalt complex, and the stability is significantly reduced.
[0145] Fig.12This is a comparison diagram of cyclic voltammetry curves after 200 bends of the capacitor constructed based on the flexible transparent carbon fiber mesh obtained in Example 5. It can be seen that after 200 bends, there is no obvious difference in the electrochemical performance of the capacitor.
[0146] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
[0147] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
Claims
1. A capacitor comprising a positive electrode, a negative electrode, and an electrolyte between the positive electrode and the negative electrode, characterized in that: Either the positive electrode or the negative electrode comprises a flexible transparent carbon fiber mesh, and the preparation method of the flexible transparent carbon fiber mesh comprises: Cobalt nitrate and the compound represented by formula (I) are applied to silk respectively, and a cobalt complex is grown in situ on the surface and / or in the pores of the silk to form silk loaded with the cobalt complex; wherein the amount of cobalt nitrate added is controlled to load 0.015-0.05 mmol per square centimeter of the silk, and the amount of the compound represented by formula (I) added is controlled to load 0.03-0.1 mmol per square centimeter of the silk; In formula (I), R1 is C 1-3 Alkyl, R2 is H or C 1-3 Alkyl, n is 1 or 2; The cobalt complex-loaded silk is heat-treated at 700-950° C. under a protective atmosphere to obtain an intermediate; Then, the intermediate is subjected to acid etching to obtain the flexible transparent carbon fiber mesh.
2. The capacitor according to claim 1, characterized in that The method for preparing the flexible transparent carbon fiber mesh also includes: Separately prepare a cobalt nitrate solution and a solution of the compound represented by formula (I); The silk is first immersed in one of the cobalt nitrate solution and the solution of the compound represented by formula (I), and then immersed in the other one.
3. The capacitor according to claim 2, characterized in that The cobalt nitrate solution and the solution of the compound represented by formula (I) respectively use water as solvent; and / or the molar concentration of the cobalt nitrate solution is 0.5-1.5 mol / L, and the molar concentration of the solution of the compound represented by formula (I) is 1.5-3.0 mol / L.
4. The capacitor according to claim 2, characterized in that The silk is first soaked in the cobalt nitrate solution for X1 min, and then soaked in the solution of the compound represented by formula (I) for X2 min, X1:X2=1.5-3:1, X1 is 15-25, and X2 is 5-15.
5. The capacitor according to claim 1, characterized in that R1 is selected from methyl, ethyl or propyl, and n is 0.
6. The capacitor according to claim 1, characterized in that The material of the silk is mulberry silk.
7. The capacitor according to claim 1, characterized in that The method for preparing the flexible transparent carbon fiber net also includes: before the heat treatment, first washing the silk loaded with the cobalt complex and drying it; and / or, the heat treatment is performed at 750-850° C. for 1-6 hours.
8. The capacitor according to claim 1, characterized in that The acid etching is performed using hydrochloric acid.
9. The capacitor according to claim 8, characterized in that The molar concentration of the hydrochloric acid is 0.5-3 mol / L.
10. The capacitor according to claim 1, characterized in that The acid etching time is controlled to be 10-60 minutes.
11. An electronic device, characterized in that: The electronic device comprises the capacitor according to any one of claims 1 to 10.
Citation Information
Patent Citations
Flexible electrode based on carbonized silk fabric and flexible battery
CN111740075A
Co and N-doped carbon nanofiber compound for lithium-oxygen battery
CN113497239A